EUS-guided pancreatic radiofrequency ablation: preclinical comparison of two currently available devices in a pig model - Barret, Maximilien; Leblanc, Sarah; Rouquette, Alexandre; Chaussade, Stanislas; Terris, Benoit; Prat, Frédéric (Endoscopy International Open, 2019)
Introduction Two devices are currently available to perform pancreatic radiofrequency ablation (P-RFA). Potential clinical indications might extend from the treatment of pancreatic cystic lesions to ablation of small pancreatic solid lesions or cytoreduction of advanced pancreatic adenocarcinomas, but more preclinical data from animal models are needed to optimize P-RFA operation. Methods P-RFA was performed under laparotomy and under endoscopic ultrasonographic guidance on the liver and pancreatic parenchyma of four live swine using the Habib EUS RFA (EMcision Ltd, London, UK) probe and the EUS-RA needle (Taewoong Medical, Gyeonggi-do, South Korea). Animals were sacrificed 2 hours after the procedure. Influence of tuning ablation time and power on tissue ablation were studied by histopathological assessment of the maximal depth of tissue damage on representative slides for each P-RFA shot.Results The Habib probe in the liver parenchyma resulted in tissue necrosis increasing within the range of 1.9 ± 0.5 mm (Power = 8 W, Time = 120 s) to 2.5 ± 1 mm (Power = 10 W, Time = 120 s). In the pancreatic parenchyma, tissue damage ranged from 3.1 ± 0.4 mm (Power = 8 W, Time = 120 s) to 2.3 ± 0.1 mm (12 W, 120 s) in depth. EUS RFA ablation of the liver parenchyma resulted in tissue damage ranging from 1.6 ± 0.2 mm (Power = 30 W, Time = 11 s) to 1.5 ± 0.1 mm (Power = 70 W, Time = 9 s); in the pancreas, ablation depth ranged from 3.6 ± 0.5 mm (Power = 30 W, Time = 15 s) to 3.8 ± 0.4 mm (Power = 70 W, Time = 11 s).Conclusion Both devices allow for effective ablation of pancreatic tissue within 1.5 to 3.8 mm around the RFA electrode, with a modest influence of tuning power settings. Specific settings are recommended for each of the devices studied. Ablation of larger lesions may require more repeat P-RFA shots in different locations rather than a simple modulation of ablation parameters.